Reaction time variations in normal aging and elderly MCI patients under various cognitive load conditions - Zhu, Yanfei; Chen, Zhuoming; Shi, Zhengkun; Chen, Junyi; Zuo, Qiankun; Yang, Zhi; Zhang, Wenjing; Li, Wanting; Lu, Siyu; Peng, Siyuan; Gou, Lei (Frontiers in Human Neuroscience, 2025)
ObjectivesTo compare reaction time parameters and accuracy rates between cognitively normal older adults and those with mild cognitive impairment (MCI) during the Stroop Color-Word Test, and to investigate how cognitive load modulates performance in MCI.MethodsSpeech audio samples (n = 1,920) were collected from 10 cognitively normal older adults and 10 MCI patients during Stroop task execution. Accuracy and reaction time were extracted. Analysis of variance and multiple comparison were used to analyze the differences in reaction time under different task conditions within the group, while the independent sample t-test was used to compare the accuracy and reaction time of the two groups under the same task. Pearson correlation analysis was used to determine the linear relationship between MOCA scores and the accuracy rate and reaction time of MCI patients in the interference suppression task.ResultsThe accuracy rate of the mild cognitive impairment (MCI) group was significantly lower than that of the control group (p < 0.05). Tasks A-D had different effects on reaction times, with significant main effects observed in both the NC group (P = 0.000, η2 = 0.637) and the MCI group (P = 0.000, η2 = 0.721). Reaction times in both groups prolonged with increasing cognitive load (p < 0.05), but the delay was more pronounced in the MCI group (p < 0.05). A positive linear correlation was found between the MoCA score and task accuracy rate (r = 0.758, P = 0.011).ConclusionDominant responses require less processing time, whereas tasks demanding interference suppression elicit slower reaction times and higher error rates. MCI patients demonstrate prolonged reaction times and greater susceptibility to proactive interference compared to controls, highlighting impaired interference control mechanisms. These findings suggest that MCI is characterized by early deficits in dominance inhibition, manifesting as reduced ability to suppress automatic responses and increased vulnerability to cognitive conflict.